PENGEMBANGAN MEDIA PEMBELAJARAN TURBAYA (MINIATUR BUDAYA) RUMAH ADAT TEMATIK TEMA 7 INDAHNYA KERAGAMAN DI KELAS IV DI SEKOLAH DASAR - Rikke Kurniawati; Lutfi Maulidya (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2022)
The main objective of this research is to produce a learning media, product of miniature traditional house. This research is a development research. Development of learning media for miniature traditional house using the research development procedure proposed by Thiagarajan. Development procedure ones used in the study includes 4 stages, namely (1) the definition stage (define), (2) design, (3) develop, (4) deployment (disseminate), but in this study at the siddeminate stage not done because of limitations time. Data collection techniques used is a questionnaire. The data analysisis used in this research is qualitative and quantutative. The results of this development research indicate that TURBAYA media (culture miniature) is very suitable for use as a medium learning after passing the media and material expert validation test. Result the average percentage value obtained from media and material experts is 86% with the criteria “very good or very eligible”, so it can be concluded that miniature media of traditional house culture can be used